A Rare Tumor in the Cervical Sympathetic Trunk: Ganglioneuroblastoma - Ozan Erol; Alper Koycu; Erdinc Aydin (Case Reports in Otolaryngology)
Ganglioneuroblastoma is a rare tumor with moderate malignancy, which is composed of mature ganglion cells and seen in sympathetic ganglia and adrenal medulla. The diagnosis is possible after cytological and immunohistochemical studies following a needle biopsy or surgical excision. There is no consensus regarding the need for chemo- or radiotherapy after surgery. In this case report, clinical behavior and diagnosis and treatment of the rare tumor cervical ganglioneuroblastoma were discussed.